Decellularisation Of porcine oesophagus - Ong, Zhen Yang (2019)
The aim of this study is to evaluate the effectiveness of the Sodium Dodecyl Sulfate (SDS) used in the decellularisation of the porcine oesophagus. In addition, which solution has the best efficiency rate in removing SDS and characterising the decellularised osesophagus by evaluating the scaffold structure.